Subgroup analysis of Japanese patients in a phase III randomized, controlled study of neoadjuvant atezolizumab or placebo, combined with nab-paclitaxel and anthracycline-based chemotherapy in early triple-negative breast cancer (IMpassion031). (25th June 2022) - Saji, Shigehira; Ohsumi, Shozo; Ito, Mitsuya; Hayashi, Naoki; Kobayashi, Kokoro; Masuda, Norikazu; Niikura, Naoki; Yamashita, Toshinari; Kiyama, Keiichiro; Hasegawa, Ayumi; Nakagawa, Shizuka; Hattori, Masaya
Abstract: Background: In the global phase III IMpassion031 study, neoadjuvant atezolizumab plus nab -paclitaxel/anthracycline-based chemotherapy improved pathological complete response in patients with early stage triple-negative breast cancer. Here, we report primary analysis results from a subgroup of Japanese patients. Methods: Patients with histologically documented, previously untreated, stage cT2–cT4, cN0–cN3, cM0 triple-negative breast cancer were randomized 1:1 to receive intravenous atezolizumab 840 mg or placebo every 2 weeks in combination with chemotherapy consisting of nab -paclitaxel intravenous 125 mg/m 2 once a week, followed by doxorubicin intravenous 60 mg/m 2 and cyclophosphamide intravenous 600 mg/m 2 every 2 weeks. Patients then underwent surgery. Pathological complete response (ypT0/is ypN0) in the intention-to-treat and PD-L1-positive (≥1% PD-L1-expressing tumor-infiltrating immune cells) populations were co-primary endpoints. Results: This subanalysis (data cutoff: 3 April 2020) included 36 patients from Japan (intention-to-treat; atezolizumab arm, n  = 17; placebo arm, n  = 19). Pathological complete response occurred in 41% ( n  = 7; 95% confidence interval, 18–67) of patients in the atezolizumab arm and 37% ( n  = 7; 95% confidence interval, 16–62) in the placebo arm. In the PD-L1-positive population, pathological complete response occurred in 50% ( n  = 5; 95% confidence interval, 19–81) of patients in the atezolizumab arm and 45% ( n  = 5; 95% confidence interval, 17–77) in the placebo arm. Treatment-related grade 3–4 adverse events occurred in 71% and 68% of patients in the respective arms. Conclusion: Atezolizumab added to neoadjuvant chemotherapy numerically improved pathological complete response versus placebo in this small exploratory analysis of Japanese patients with early stage triple-negative breast cancer, a trend directionally consistent with the global study results. No new safety signals were identified. Abstract : The efficacy and safety of atezolizumab plus neoadjuvant nab -paclitaxel and anthracycline-based chemotherapy in Japanese patients in the IMpassion031 study were consistent with those observed in the global study population.